EGYPT TRANSITION TO DEMOCRACY; THE DEMOCRACY CONSOLIDATION OF MOHAMMAD MORSI - Erdhieta Ghaisani Puteri (HI 16 UMY 045, 2016)
*45 Democracy had been an issue in Egypt ever since 1952 revolution. The 2010 Arab Spring, however, had woken up Egyptian towards the democracy which led to the 2011 democracy revolution which was also known as the day of rage. The 2011 revolution became a momentum for Egyptian transition to democracy to enter a new phase. The fall of President Husni Mubarak’s authoritarian regime was cheerfully celebrated by the people of Egypt. Following the event, the Supreme Council of Armed Forces took control over Egypt transition to democracy. Under SCAF, the parliamntary and presidential election was held and it resulted on the elevation of Mohammad Morsi as the fifth of Egypt and the first president from the civilian. However, a year after Mohammad Morsi was chosen by Egyptian people as the 2012 new president of Egypt, Mohammad Morsi being ousted by the military. Thus, this paper is aimed to analyze process of Egypt’s democracy transition under the regime of Mohmammad Morsi by using two theories as the tools of analysis. The first theory is theory of Transition to Democracy which was brougt by Samuel P. Huntington, and the second theory is the Democracy Consolidation initated by Larry Diamond. Keyword: Democracy Consolidation, Mohammad Morsi, Muslim Brotherhood, Supreme Council of Armed Forces (SCAF), Egypt Military, Egypt Armed Forces (EAF